Kesenjangan Gizi di Balik Anemia Maternal: Sorotan pada Asupan Energi dan Zat Besi pada Ibu Hamil di Bandung - Ananda Salma Nurhalimah; Isti Kumalasari; Asti Dewi Rahayu Fitrianingsih; Widya Astuti (Media Gizi Kesmas, 2026)
Background: Pregnancy anemia is one of the most important global problems in public health, and approximately 40% of women suffer from it worldwide. According to the World Health Organization (WHO), his condition, is defined as a hemoglobin concentration below 11 g/dL and may compromise both maternal and fetal health. Objectives: This study was conducted to determine the association between macro- and micronutrient adequacy with anemia prevalence in third-trimester pregnant women in the Greater Bandung region. Methods: A quantitative cross-sectional study was conducted among 82 third-trimester pregnant women recruited as sample using sampling of Bandung City and Bandung Regency. Structured interviews, 24-hour recall of diet, and measurement of hemoglobin by digital hemoglobinometer were used for data collection. Chi-square test and Fisher’s exact test were performed for statistical analyses. Results: The proportion of anemia in the third trimester pregnant women was about 32.9%. The only significant associations with anemia were observed for insufficient energy (OR=3.892, 95% CI:1.03–14.65; p=0.035) and iron intake (OR=14.213, 95% CI: 0.80–250.96; p=0.013). Protein, fat, carbohydrate, folic acid, vitamin B12, or vitamin C were not significantly associated. Conclusion: Adequacy energy and iron intake were the major factors associated with anemia among pregnant women during the third semester. Tailored dietary counselling and iron supplementation programs are recommended as focused nutritional intervention to decrease anemia-specific deficits. Key limitations include the cross-sectional design and the use of a single 24-hour dietary recall, which may limit causal inference and dietary assessment. Further studies should involve larger sample sizes and longitudinal designs to confirm these findings and provide evidence for maternal nutrition policy.